The potential of natural waste for production of environmental friendly biodegradable films - Norashikin, Mat Zain (Penerbit UMP, 2009)
Plastic in the environment is regarded to be hazard, since the material is inert. Nondegradable plastics accumulate at the rate of 25 million tonnes per year. According to an estimate more than I 00 million tonnes of plastic is produced every year all over the world. In an effort to protect the environment, biodegradable film has been develop from natural waste for packaging application.